상온분말분사법에 의해 Yttria Stabilized Zirconia 코팅된 STS304 표면 경도 특성 - 임지호; Ji-ho Lim; 박춘길; Chun-kil Park; 이용석; Yong-seok Lee; 공영민; Young-min Kong; 강권호; Kweon Ho Kang; 김형순; Hyung Sun Kim; et al. (대한금속·재료학회지, 54(3), 2016)
To improve the surface harndess of the STS304, Yttria stabilized zirconia (YSZ) films with nano-sized grain were deposited by an aerosol-deposition (AD) method. Coating layers showed dense structure and had ~5μm thickness. When 3 mol% YSZ powders with tetragonal phase were deposited on STS304 substrate, tetragonal structure was transformed to cubic structure due to the high impact energy during the AD process. At the same time, strong impact by YSZ particles allowed the austenite phase in STS304 to be transformed into martensite phase. Surface hardness measured with nano indentor showed that YSZ coated film had 11.5 GPa, which is larger value than 7 GPa of STS304.